The territorial labelling of a heritage site in the north eastern Cape Drakensberg, South Africa- the case of the Linton Cave - (:unkn) unknown (My University, 2017)
This study shows how the territorial labelling of a specific heritage site in the NE Cape Drakensberg, South Africa contributed to a contested, fragile and obscure national identity, in the form of figures on a nation’s coat of arms. The methodology analysed the language harnessed by both the South African government and the South African museum in Cape Town where the excised Linton Panels reside. Furthermore, a number of maps were analysed, showing how the area was, and still is, neglected and marginalized. Moreover, a few academic papers were studied, showing how the cave was cut into, and panels excised for transport to the South African Museum, and then no further significance, or protection, attached to the extremely noteworthy shelter from whence the panels came. The territorial area today is marked by deep spatial and cultural inequalities, with extremely vulnerable communities living close by, despite half-hearted and incipient measures to revive the economy of the area.
Keywords: African Research